Consumption behavior of university students in Islamic economics perspective - Chandra, Brillyan Octaviani (Journal of Islamic Economics Lariba, 2016)
This study aims to analyze consumption behavior of students of Department of Islamic Economics of University of Islam Indonesia, particularly class of 2012, whether it is in accordance with the Islamic perspective or not and how the students’ social environment does affect the consumer behavior. This study applies descriptive quantitative analysis which is done by choosing 50 respondents aged between 20-24 year old as sample based on Purposive Sampling method. The writer also uses questionnaires in gathering the data and double linear analysis technique in processing the data. In this study, the writer finds that the consumer behavior of the Ekis FIAI UII students, particularly class of 2012, has actually been in accordance with the principle of aqidah, amaliyah, and spirituality, even though it has not yet represented the simple and modest principle. According to ‘t’ test, it shows that the adherent group variable has no significant influence to the Islamic consumer behavior of the 2012 Ekis students since the value of ‘t’ is smaller than the table of ‘t’, which is 0.728 < 2.011. The value of ‘t’ of the family variable is about 2.506, meaning that family has significant impact towards Islamic consumer behavior. From the independent variables, it is found that the adherent and family variable do not significantly influence the Islamic consumer behavior. The adjusted R square is 0,133, meaning that 13,3% of the Islamic consumer behavior of 2012 Ekis students is affected by family.